Amitriptyline and bromazepam in the treatment of vibratory angioedema: which role for neuroinflammation?. Issue 6 (22nd July 2014) - Guarneri, Fabrizio; Guarneri, Claudio; Marini, Herbert Ryan
Abstract Vibratory angioedema is a rare form of physical urticaria, hereditary or acquired, which occurs at body sites exposed to vibrations. Pathogenic mechanisms of disease are not completely clear and, consequently, current pharmacological treatment is sometimes unsatisfactory. We report the case of a horn player affected by acquired vibratory angioedema, relapsing after prolonged use of the instrument and resistant to systemic antihistamines and corticosteroids, which successfully responded to therapy with low doses of amitriptyline and bromazepam. A neuroinflammatory mechanism can be likely implicated in the pathogenesis of vibratory angioedema, in line with many different cutaneous/mucosal diseases involving a complex interplay of homeostatic/allostatic systems. Furthermore, in mucosal diseases, such as vibratory angioedema, physical/psychological stressors have a relevant role. In such cases, because of the complex interplay between nervous and immune system, the pharmacological activity of benzodiazepines and typical antidepressants may downregulate neuroinflammation.